Duodenal switch versus Roux‐en‐Y gastric bypass for morbid obesity: systematic review and meta‐analysis of weight results, diabetes resolution and early complications in single‐centre comparisons. Issue 7 (25th March 2014) - Hedberg, J.; Sundström, J.; Sundbom, M.
Summary Long‐term weight loss after Roux‐en‐Y gastric bypass (RYGB) in super‐obese patients has not been ideal. Biliopancreatic diversion with duodenal switch (DS) is argued to be better; however, additional side effects are feared. The aim of the present study was to determine differences in results after DS and RYGB in publications from single‐centre comparisons. A systematic review of studies containing DS and RYGB performed at the same centre was performed. Outcome data were weight results, resolution of comorbid conditions, perioperative results and complications. Main outcome was difference in weight loss after DS and RYGB. Secondary outcomes were difference in resolution of comorbidities, perioperative results and complications. The final analysis included 16 studies with in total 874 DS and 1, 149 RYGB operations. When comparing weight results at the longest follow‐up of each study, DS yielded 6.2 (95% confidence interval 5.0–7.5) body mass index units additional weight loss compared with RYGB, P < 0.001. Operative time and length of stay were significantly longer after DS, as well as the risk for post‐operative leaks, P < 0.05. DS is more effective than RYGB as a weight‐reducing procedure. However, this comes at the price of more early complications and might also yield slightly higher perioperative mortality.